Internet of things (IOT) untuk pembelajaran sains kontekstual pada calon guru sains - Rony Harianto; Moh Fausi; Khotibul Umam; Zurni Rizqiyati (SAP (Susunan Artikel Pendidikan), 2025)
The development of digitalization needs in the world of education is increasingly rapid, accompanied by the growing needs of schools that require prospective teachers to possess the skills to utilize internet-integrated learning. This study aims to explore the application of the Internet of Things (IoT) in contextual science learning for pre-service science teachers. This study uses a descriptive case study approach with a mixed-methods design (quantitative and qualitative). Data were collected through questionnaires, interviews, and observations involving 46 pre-service science teachers. The findings show that the use of IoT strengthens the understanding of scientific concepts, increases student engagement, and supports critical thinking skills. However, some technical challenges were encountered during the initial implementation phase, such as difficulties in operating the devices. The implications of this study highlight the need for enhanced technical training for pre-service teachers and the provision of adequate infrastructure. The conclusion of this study is that the integration of IoT in science learning has a positive impact on the quality of education and prepares pre-service teachers to optimize technology in their pedagogical practices in the future.